Phenomenological Study: Nurses' Experiences In Treating And Referring Penetrating Trauma Patients At The Arjasa Public Health Center, Sumenep Regency - Alfien Yoesra; Asti Melani Astari; Alfrina Hany (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Arjasa Health Center is a health center in a remote area in the Kangean Islands, Sumenep Regency. The distance from the Arjasa health center to the referral hospital is 88 miles (142 km). The only access to the referral hospital is by sea. The length of the sea journey to the referral hospital from the Arjasa health center is 9-10 hours. Cases of penetrating trauma at the Arjasa Health Center in 2021 were eight patients. All the penetrating trauma patients after the primary and secondary surveys at the Arjasa Public Health Center were then referred to a referral hospital in Sumenep Regency. This study aims to explain nurses' experience in treating and referring penetrating trauma patients at the Arjasa Public Health Center. This study uses qualitative research with a hermeneutic phenomenological study approach which is analyzed using interpretative phenomenological analysis. The results of the study found nine themes: 1) feeling afraid that the patient's condition would worsen when referred, 2) limited advice and infrastructure at the puskesmas, 3) the situation and condition of the patient who had to be referred, 4) weather conditions when referring, 5) the distance from the referring hospital, 6) the presence of surgeon specialists at the puskesmas, 7) the completeness of supporting facilities and infrastructure, 8) improving the status of the puskesmas and 9) increasing the skills of nurses. The theme explains the feelings, challenges and hopes of nurses working at the Arjasa Public Health Center. Abstrak: Puskesmas Arjasa merupakan puskesmas di wilayah terpencil yang berada di Kepulauan Kangean, Kabupaten Sumenep. Jarak dari puskesmas Arjasa menuju rumah sakit rujukan adalah 88 mill (142 km). Satu-satunya akses menuju rumah sakit rujukan adalah dengan melewati lautan. Lama perjalanan laut menuju rumah sakit rujukan dari puskesmas Arjasa adalah 9-10 jam. Kasus trauma tembus di puskesmas Arjasa pada tahun 2021 sebanyak delapan pasien. Semua pasien trauma tembus tersebut setelah dilakukan tindakan primary survey dan secondary survey di puskesmas Arjasa kemudian dirujuk ke rumah sakit rujukan yang berada di Kabupaten Sumenep. Penelitian ini bertujuan untuk menjelaskan pengalaman perawat dalam merawat dan merujuk pasien trauma tembus di puskesmas Arjasa. Metode dalam penelitian ini menggunakan kualitative research dengan pendekatan hermeneutic phenomenological study yang dianalisis menggunakan interpretative phenomenological analysis. Hasil penelitian menemukan Sembilan tema: 1) merasa takut kondisi pasien memburuk saat dirujuk, 2) keterbatasan saran dan prasarana di puskesmas, 3) situasi dan kondisi pasien yang harus dirujuk, 4) keadaan cuaca saat merujuk, 5) jauhnya rumah sakit tempat merujuk, 6) adanya dokter spesialis bedah di puskesmas, 7) kelengkapan sarana dan prasarana penunjang, 8) Peningkatan status puskesmas dan 9) peningkatan skill perawat. Tema tersebut menjelaskan perasaan, tantangan dan harapan perawat yang bekerja di puskesmas Arjasa.